Cost analysis of a sequential antimicrobial therapy protocol in patients with pneumonia: A multicenter study - Flaviane Gecler Parreira; Juan Vicente da Cunha Leal; Aline Correa de Araujo; Amanda Mota Conceição; Amanda Migliorini do Nascimento; Carolina Serra Cabo Jogaib; Sabrina Calil-Elias; Jéssica Pronestino de Lima Moreira (PLoS ONE, 2026)
Pneumonia is one of the leading causes of hospitalization and mortality due to infectious diseases and is also responsible for a substantial proportion of antimicrobial prescriptions. This study aimed to analyze the clinical outcomes and the economic implications associated with a sequential antimicrobial in hospitalized patients with pneumonia. This was a multicenter, retrospective, observational cost analysis study conducted in four private Brazilian hospitals between January 2022 and December 2023. A total of 185 medical records from patients undergoing the sequential therapy protocol were included. Clinical outcomes, length of hospital stay, acceptability among physicians of pharmacist-led interventions for switching the route of administration, and the direct costs related to medications and human resources were assessed according to a microcosting methodology. Among the included patients, 74.6% transitioned to the oral route, and 88.4% showed a positive clinical outcome. Sequential therapy was associated with a significant reduction in mean length of stay (10.1 vs. 14.7 days; p = 0.024) and was associated with 55% lower treatment costs, corresponding to an estimated cost avoidance of US$ 4,529.96. The findings suggest that sequential antimicrobial therapy is an safe and economically advantageous strategy that contributes to the rational use of antimicrobials and the optimization of hospital resources.